Annotated checklist of Dryopidae and Heteroceridae (Coleoptera: Byrrhoidea) of Iran - Mascagni, Alessandro; Jäch, Manfred A.; Ostovan, Hadi; Ghahari, Hassan (Zootaxa, 2016)
The distribution of Dryopidae and Heteroceridae (Coleoptera: Byrrhoidea) of Iran is summarized. A total of ten species of Dryopidae in three genera (Dryops Olivier, Parahelichus Löbl & Smetana, and Praehelichus Löbl & Smetana), and 18 species of Heteroceridae in two genera (Augyles Schiödte and Heterocerus Fabricius) are listed. Augyles hispidulus (Kiesenwetter, 1843) (Heteroceridae) is recorded from Iran for the first time.